Metaphyseal burst sign: A secondary sign on MRI of subchondral insufficiency fracture of the knee. Issue 6 (16th August 2018) - Vidoni, Alessandro; Shah, Rachit; Mak, Davina; Beale, David; Beale, Sioned; James, Steven; Botchu, Rajesh
Abstract: Introduction: To describe a novel secondary sign of subchondral insufficiency fracture of the knee, metaphyseal burst sign (soft tissue oedema in the meta‐epiphyseal region of the affected condyle). Methods: An electronic database research of 7926 knee MRI examinations was performed. Forty‐eight scans were included in the study. The diagnosis of subchondral insufficiency fracture (SIF) was confirmed in a consensus review by one fellowship trained musculoskeletal (MSK) radiologist and one radiology fellow. The presence of metaphyseal burst sign was evaluated in the cohort. Results: Forty‐one patients were included in the study (21 males, 20 females). The mean age was 61.5 years (range 41–80 years). The anatomical location was medial femoral condyle ( n  = 28), the lateral femoral condyle ( n  = 5) and medial tibial condyle ( n  = 8). The metaphyseal burst sign was present in 45 of the 48 scans reviewed. The average craniocaudal length of the soft tissue oedema defined as metaphyseal burst sign was 7 cm (range 10.5 to 4.5). Conclusion: The metaphyseal burst sign is an early, indirect sign of SIF.